Assessment of individual water quality index parameter in Terengganu river, Malaysia - Mohd Khairul Amri, Kamarudin; Nalado Aliyu, Muhammad; Noorjiwa, Abd Wahab; Ahmad Shakir, Mohd Saudi (2017)
Water quality is a state of biological, physical, and chemical characteristics of water in collaboration with anticipated use and a set of standards. Samplings were taken in wet and dry seasons from twenty-nine stations within the river basin. Six parameters were used base on National Water Quality Standard (NWQS). Individual Water Quality Index (WQI) is used to compare the parameters with WQI table to show results on many impacts of natural and anthropogenic factors. Six parameters have been calculated to have the WQI which is wet season has a range of 62.10 to 75.46 with a mean of 72.81, while dry season ranging from 56.3 74.14 with an average of 70.47 which based on water quality classification is slightly polluted. It is suggested that monitoring and treatment should be appropriately carried out on measured parameters that fall in Class III and IV along with the river.